public service of local government organizations - singlee, kesirin (Journal of Humanities and Social Sciences Mahamakut Buddhist University Isan Campus, 2023)
This article discusses public services of local governments. This is an activity that is important to people in using public services in the locality. Whether taking care and providing public services for the benefit of local people as required by law It meets the needs of society and the individual members of society in order to receive services from the state. on matters that the private sector or private enterprises cannot respond Whether it is a public service. in terms of providing protection for the safety of life and property and provide various utilities such as garbage collection, solid waste, swimming pool operations or public transport etc.